1989
DOI: 10.1017/s0144686x00013520
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Quality of Life in NHS Nursing Homes and a Long-stay Ward for the Elderly

Abstract: An observational study was carried out in order to measure the quality of life of elderly people in two different types of long-stay care (two NHS nursing homes and a hospital ward). This formed part of a wider evaluation study of these two forms of institutional care. Qualitative techniques provided insights into the behaviours, moods, interactions and atmospheres in the settings, which were difficult to measure using traditional survey approaches. The observational study showed that it is.essential not to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…Studies have found that QoL is related to home life and family relationships (Aureli and Baldazzi 2002;Farquhar 1995;Hall 1976), health (Clark and Bowling 1989;Farquhar 1994Farquhar , 1995Hall 1976;Michalos et al 2000Michalos et al , 2001, economic resources (Arnold 1991;Aureli and Baldazzi 2002;Lundberg and Thorslund 1996;Shek 2005), community involvement and social support network (Hughes 1993;Schalock et al 1989), gourmet cooking and buying works of art (Michalos 2005), etc. Few studies, however, have been done on the role of ICTs in QoL.…”
mentioning
confidence: 96%
“…Studies have found that QoL is related to home life and family relationships (Aureli and Baldazzi 2002;Farquhar 1995;Hall 1976), health (Clark and Bowling 1989;Farquhar 1994Farquhar , 1995Hall 1976;Michalos et al 2000Michalos et al , 2001, economic resources (Arnold 1991;Aureli and Baldazzi 2002;Lundberg and Thorslund 1996;Shek 2005), community involvement and social support network (Hughes 1993;Schalock et al 1989), gourmet cooking and buying works of art (Michalos 2005), etc. Few studies, however, have been done on the role of ICTs in QoL.…”
mentioning
confidence: 96%
“…Similarly, the work domain corresponds to the employment domain (Lundberg and Thorslund, 1996). The accommodation corresponds to the housing, residential, security, environment, home, material, and privacy domains (Clark and Bowling, 1989;Norcross, 1990;Pynoos and Regnier, 1991;Hughes, 1993;Farquhar, 1994;Lundberg and Thorslund, 1996;Chan et al, 2002). The finance domain corresponds to the economic resource, and property domains (Arnold, 1991;Lundberg and Thorslund, 1996).…”
Section: Quality Of Life In Older Adults: Benefitsmentioning
confidence: 97%
“…The friendship domain corresponds to community relationship, community involvement, support network, social functioning, social contact, and interpersonal relation domains (Schalock et al, 1989;Norcross, 1990;Arnold, 1991;Hughes, 1993;Farquhar, 1994;Stewart and King, 1994;Chan et al, 2002). The health domain corresponds to the health, nutrition, functioning, comfort, pain, energy, independence, symptom, ability, and mobility domains (Clark and Bowling, 1989;Norcross, 1990;Arnold, 1991;Kutner et al, 1992;Hughes, 1993;Farquhar, 1994;Stewart and King, 1994;Lundberg and Thorslund, 1996;Chan et al, 2002). The self-domain corresponds to the self, happiness, mental health, psychological well-being, and emotional functioning domains (Clark and Bowling, 1989;Arnold, 1991;Kutner et al, 1992;Hughes, 1993;Farquhar, 1994;Stewart and King, 1994).…”
Section: Quality Of Life In Older Adults: Benefitsmentioning
confidence: 98%
See 1 more Smart Citation
“…This usually involves some combination of in-depth interviews with residents, staff, and others who visit the setting on a less regular basis such as relatives and other professionals coupled with observation of the setting over a sufficient period of time to cover both the daily/weekly routine. Different forms of observation have been developed from the straightforward participant observer 34 to the more exacting timed observation. 35 Such a multimethod approach to research is bound to have its difficulties, for it means acknowledging a wide range of group interests, unequal power relations and varied definitions of what constitutes successful service provision and quality.…”
Section: -32mentioning
confidence: 99%